Developing retinal biomarkers for the earliest stages of Alzheimer's disease: What we know, what we don't, and how to move forward. Issue 1 (8th January 2020) - Alber, Jessica; Goldfarb, Danielle; Thompson, Louisa I.; Arthur, Edmund; Hernandez, Kimberly; Cheng, Derrick; DeBuc, Delia Cabrera; Cordeiro, Francesca; Provetti‐Cunha, Leonardo; den Haan, Jurre; Van Stavern, Gregory P.; Salloway, Stephen P.; et al.
Abstract: The last decade has seen a substantial increase in research focused on the identification, development, and validation of diagnostic and prognostic retinal biomarkers for Alzheimer's disease (AD). Sensitive retinal biomarkers may be advantageous because they are cost and time efficient, non‐invasive, and present a minimal degree of patient risk and a high degree of accessibility. Much of the work in this area thus far has focused on distinguishing between symptomatic AD and/or mild cognitive impairment (MCI) and cognitively normal older adults. Minimal work has been done on the detection of preclinical AD, the earliest stage of AD pathogenesis characterized by the accumulation of cerebral amyloid absent clinical symptoms of MCI or dementia. The following review examines retinal structural changes, proteinopathies, and vascular alterations that have been proposed as potential AD biomarkers, with a focus on studies examining the earliest stages of disease pathogenesis. In addition, we present recommendations for future research to move beyond the discovery phase and toward validation of AD risk biomarkers that could potentially be used as a first step in a multistep screening process for AD risk detection.